Association between dietary patterns and adiposity from 4 to 7 years of age - Durão, C (2017)
Objective: The present study aimed to evaluate the association of 4-year-old children’s dietary patterns with adiposity at 7 years, according to child’s sex, using a conceptual model. Design: Prospective cohort study. Diet was assessed using an FFQ. Age- and sex-specific BMI standard deviation scores (Z-scores) were defined according to the WHO. Fat mass percentage (FM%), fat mass index (FMI) and waist-to-height ratio (WHtR) were also considered, converted into Z-scores using sex-specific means and standard deviations of the current sample. Dietary patterns were identified by latent class analysis and their association with adiposity was estimated by linear regression models. Setting: Population-based birth cohort Generation XXI (Porto, Portugal, 2005–2006). Subjects: Children (n 3473) evaluated at both 4 and 7 years of age. Results: Three dietary patterns were identified: high in energy-dense foods (EDF); low in foods typically consumed at main meals and intermediate in snacks (Snacking); and higher in vegetables and fish and lower in EDF (Healthier, reference). The EDF dietary pattern at 4 years of age was positively associated with later BMI only in girls (β=0·075, 95 % CI 0·009, 0·140, P-interaction =0·046). The EDF dietary pattern was also associated with other adiposity indicators only in girls (FMI: β=0·071, 95 % CI 0·000, 0·142; WHtR: β=0·094, 95 % CI 0·023, 0·164). Snacking was not significantly associated with any marker of adiposity in either girls or boys. Conclusions: Although dietary patterns and adiposity persisted across the two ages in both sexes, EDF at 4 years of age increased adiposity at 7 years of age only in girls.